A hybrid decision-making model for sustainable supplier evaluation in electronics manufacturing. (June 2021) - Chang, Tai-Wu; Pai, Chun-Jui; Lo, Huai-Wei; Hu, Shu-Kung
Graphical abstract: Highlights: This study proposes a SSES framework in electronics manufacturing. We develop a hybrid model that combines modified ITARA and ROMETHEE-AL techniques. The addition of the aspiration level concept makes the analysis results more reliable. An electronic manufacturing case example is used to verify the usefulness and applicability. Abstract: The rapid development of information technology and electronic products has had a profound impact on global business activities and the quality of human life. To maintain competitiveness among enterprises, contribute to society, and protect the environment while maintaining profits, electronics manufacturers must move toward sustainable development. This paper proposes the following four dimensions for sustainable supplier evaluation and selection (SSES): economic, social, environmental, and institutional sustainability. These dimensions can be subdivided into 20 criteria, which constitute the SSES framework of electronics manufacturing. A modified indifference threshold-based attribute ratio analysis (ITARA) technique is proposed to obtain the objective weights of the criteria and the preference ranking organization method for enrichment evaluation based on aspiration level concept (PROMETHEE-AL) method is applied to integrate the performances of sustainable suppliers and determine their rankings. The modified ITARA and PROMETHEE-AL methods are integrated as a hybrid decision-making analysis model, which improves the conventional ITARA and PROMETHEE methods and introduces the concept of aspiration level to enhance their practical applicability. In addition, through model comparisons and sensitivity analysis, the robustness of the proposed model is demonstrated and more potential management information and suggestions are obtained. The study results can help decision-makers in the industry and academic researchers to better understand how systematic supplier selection can be conducted in electronics manufacturing. This study provides a complete SSES approach to support decision-makers and practitioners in easily determining the performance of alternative suppliers. For researchers, the proposed decision-making model can be used as a research basis for SSES to facilitate the development of other more forward-looking methodologies.